Publik Figur Otoritatif Perspektif Surah Al Muzammil - Muhammad Minan (LP2M Universitas PTIQ Jakarta, 2015)
This paper reviews how each Muslim places himself as a public figure, based on the example of the Prophet Muhammad in practicing surah Al-Muzammil 1-5. This is because every Muslim in person is the main figure in real life or at least in the family sphere. By understanding the situation and conditions when the Messenger of Allah accepted the chapter Al-Muzammil, and adapted to the present developments, every Muslim must become an attractive figure, well-known, and be a role model for his fellow man